TINGKAT PENGETAHUAN DAN UPAYA PREVENTIF IBU PKK DALAM PENCEGAHAN COVID-19 DI MASA PANDEMI DI WILAYAH RW 11, KELURAHAN METESEH, SEMARANG. - Dinar Matsnanuha Khalista; Nurjazuli Nurjazuli; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2021)
COVID-19 is an infectious disease which causes by RNA virus with symptoms like fever, cough, cold as the first symptoms that shows. COVID-19 can attack every age whether it’s infant, toddler, teenager, adult even worst for elderly. This study was done because it found 1 from 5 member of PKK’s Organization infected by COVID-19. This study made to know about members of PKK’s Organization’s knowledge, and to know the relation between knowledge and preventive behavior and Washing hands habit. This study is an observational analytic and used a cross-sectional design with using total sampling technique and having 60 members of PKK’s organization as respondents in total, and the data was collected by self-administrated questionnaire. The independent variable of this study is the knowledge of respondents about COVID-19 and the dependent variable are preventive behavior from respondent for dealing with this COVID-19 pandemic, and washing hands habit of respondents to prevent COVID-19. This study was using chi-square test. This study showed that there was relation between respondents’ knowledge and preventives behavior (p-value = 0.001), and no relation between respondents’ knowledge and respondents’ washing hands habit (p-value = 0.785), it concluded that there was relationship between respondents’ knowledge with their preventives behavior because it was found significantly that low respondents’ knowledge about steps of COVID-19’s preventives made respondents’ preventives behavior bad and no relationship washing hands habit because it found insignificant result caused by the data was too little and it makes some respondents answered the same point and made the imbalance to the result.